2002
DOI: 10.1042/cs1020645
|View full text |Cite
|
Sign up to set email alerts
|

Increased cationic amino acid flux through a newly expressed transporter in cells overproducing nitric oxide from patients with septic shock

Abstract: Increased production of nitric oxide (NO) is thought to be a factor in the pathogenesis of many human diseases - among them the hypotension that often accompanies sepsis. The supply of the cationic amino acid arginine is known to be rate-limiting for NO production. We hypothesized that cationic amino acid transport might be increased in cells producing excess NO from patients with septic shock. Peripheral blood mononuclear cells were isolated from patients with sepsis and from healthy control subjects. The rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 17 publications
(21 reference statements)
0
21
0
1
Order By: Relevance
“…In peripheral blood mononuclear cells (PBMCs) in nonpregnant subjects, transport systems y ϩ and y ϩ L have been identified, contributing 13.7% and 86.3%, respectively, to total cationic amino acid transport. 16 In sepsis, cationic amino acid (L-lysine) uptake has been dem-onstrated to be significantly increased in association with increased NO production. This has been demonstrated to be almost entirely because of increase in the activity of the y ϩ transporter (contribution to total uptake increased from 13.7% to 49.5%) with a corresponding induction of CAT-2 mRNA expression and no significant change in uptake by system y ϩ L. 16 In patients with chronic renal failure and uraemia (a condition associated with increased circulation of proinflammatory cytokines), alterations in the L-arginine-NO pathway in PBMCs are characterized by a significant increase in system y ϩ activity with no change in system y ϩ L activity.…”
mentioning
confidence: 99%
“…In peripheral blood mononuclear cells (PBMCs) in nonpregnant subjects, transport systems y ϩ and y ϩ L have been identified, contributing 13.7% and 86.3%, respectively, to total cationic amino acid transport. 16 In sepsis, cationic amino acid (L-lysine) uptake has been dem-onstrated to be significantly increased in association with increased NO production. This has been demonstrated to be almost entirely because of increase in the activity of the y ϩ transporter (contribution to total uptake increased from 13.7% to 49.5%) with a corresponding induction of CAT-2 mRNA expression and no significant change in uptake by system y ϩ L. 16 In patients with chronic renal failure and uraemia (a condition associated with increased circulation of proinflammatory cytokines), alterations in the L-arginine-NO pathway in PBMCs are characterized by a significant increase in system y ϩ activity with no change in system y ϩ L activity.…”
mentioning
confidence: 99%
“…KAT, ADMA'nın hem hücreden dışarıya salınmasında, hem de hücreye alınmasında görevlidir. Konjestif kalp yetmezliği, akut böbrek yetmezliği ve septik şok gibi bazı klinik durumlarda KAT ekspresyonunun değişmiş olduğu bildirilmiştir [22][23][24]. KAT tarafından dolaşıma taşınan ADMA'nın, biyolojik olarak aktif olup olmadığı veya yüksek plazma konsantrasyonunun yüksek hücre içi seviyelerin bir belirteci olup olmadığı bilinmemektedir.…”
Section: Adma'nın Yıkılmasıunclassified
“…64 Altered expression of CAT has been implicated in several clinical conditions, including congestive heart failure, chronic and acute renal failure, and septic shock. [65][66][67] It has been shown that system yϩ is capable of transporting both ADMA and SDMA across the cell membrane. 68 Changes in the expression of CAT may therefore not only influence the interorgan transport and cellular uptake of arginine, but also of ADMA and SDMA.…”
Section: Role Of Amino Acid Transportersmentioning
confidence: 99%